Diffuse reflectance spectroscopy of solid solutions in the Ag7PS6-Ag8GeS6 system - Malakhovska Tetyana; Малаховська Тетяна; Pogodin Artem; Погодін Артем; Filep Mykhailo; Філеп Михайло; Filep Mihály; Studenyak Yaroslav; Студеняк Ярослав; Oleksandr Kokhan; Кохан Олександр; Oksana Zubaka; et al. (My University, 2023)
Abstract. Samples of Ag7+x(P1–xGex)S6 (x = 0, 0.1, 0.25, 0.33, 0.5, 0.75, 1.0) solid solutions were obtained in the form of microcrystalline powders by grinding in an agate mortar. The diffuse reflectance spectra of the obtained Ag7+x(P1–xGex)S6 samples were studied in the spectral range 200 to 1400 nm at 293 K. The spectral dependences were analyzed using multilevel approximation by applying the Kubelka–Munk function and the Tauc method. It has been found that for Ag7+x(P1-xGex)S6 solid solutions, a red shift of the reflection edge beginning is observed with increasing the Ge content. The pseudo-gap values of Ag7+x(P1–xGex)S6 solid solutions was estimated by the Tauc method. It was found that the heterovalent cationic substitution P+5 → Ge+4 within the anionic sublattice leads to a monotonic nonlinear decrease in the pseudo-gap values.

Резюме. Зразки твердих розчинів Ag7+x(P1–xGex)S6 (x = 0, 0.1, 0.25, 0.33, 0.5, 0.75, 1.0) одержано у формі мікрокристалічних порошків шляхом розмелювання в агатовій ступці. Спектри дифузного відбиття отриманих зразків твердих розчинів Ag7+x(P1–xGex)S6 досліджено у спектральному діапазоні 200…1400 нм при температурі 293 K. Спектральні залежності проаналізовано багаторівневою апроксимацією з використанням функції Кубелки–Мунка та графічного методу Таука. Встановлено, що для твердих розчинів Ag7+x(P1–xGex)S6 при збільшенні вмісту Ge спостерігається червоний зсув початку краю відбиття. Графічним методом Таука оцінено псевдоширину забороненої зони твердих розчинів Ag7+x(P1–xGex)S6. Установлено, що гетеровалентне катіонне заміщення P +5 → Ge+4 у межах аніонної підґратки приводить до монотонного нелінійного зменшення псевдоширини забороненої зони.
Спектроскопія дифузного відбиття твердих розчинів у системі Ag7PS6-Ag8GeS6
Contents: http://journal-spqeo.org.ua/n2_2023/n2_2023_contents.htm
Editorial Board: http://journal-spqeo.org.ua/EditorialBoard.html
Keywords: optical properties; diffuse reflectance spectroscopy; microcrystalline powder; Tauc method; solid solution